2014
DOI: 10.1039/c3ee42704h
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of solid-state electrolyte coated cathode materials with superior high-voltage cycling behavior for lithium ion battery application

Abstract: A highly lithium ionic conductive solid-state electrolyte coating layer significantly increases cathode performance in lithium ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
292
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 384 publications
(306 citation statements)
references
References 57 publications
13
292
1
Order By: Relevance
“…However, there is surprisingly little, and conflicting, data on the basic transport properties of the NMC family of compounds. [19][20][21][22][23] Wu et al, 19 and Hao 20 measured using the GITT technique the chemical diffusivity of NMC 333 based composite electrodes (e.g., NMC powder combined with polymer binder and carbon additive) as a function of lithium content, and reported results differing by two orders of magnitude from each other. Furthermore, whereas Hao 20 reported that the chemical diffusivity of NMC 333 is nearly independent of lithium content, Wu et al 19 found two orders of magnitude variation of lithium diffusivity with lithium content.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is surprisingly little, and conflicting, data on the basic transport properties of the NMC family of compounds. [19][20][21][22][23] Wu et al, 19 and Hao 20 measured using the GITT technique the chemical diffusivity of NMC 333 based composite electrodes (e.g., NMC powder combined with polymer binder and carbon additive) as a function of lithium content, and reported results differing by two orders of magnitude from each other. Furthermore, whereas Hao 20 reported that the chemical diffusivity of NMC 333 is nearly independent of lithium content, Wu et al 19 found two orders of magnitude variation of lithium diffusivity with lithium content.…”
mentioning
confidence: 99%
“…Furthermore, whereas Hao 20 reported that the chemical diffusivity of NMC 333 is nearly independent of lithium content, Wu et al 19 found two orders of magnitude variation of lithium diffusivity with lithium content. Gu et al 21 and Li et al 23 measured the lithium ion diffusivity of lithiated NMC 333 , also in the form of composite electrodes, using cyclic voltammetry (CV). The results differed by four orders of magnitude between the two studies (10 −14 cm 2 /s vs. 10 −10 cm 2 /s).…”
mentioning
confidence: 99%
“…Determining Entropic Heat Flow.-In order to differentiate between the parasitic heat flow during charge and discharge, it is necessary to know the entropic heat flow during both charge and discharge given bẏ q entropy ± =q total ± −q over potential ± −q parasitic ± [5] where + denotes charge and -discharge. However,q parasitic± was the original quantity of interest, and it is therefore not possible to calculatė q entropy ± exactly.…”
Section: Electrochemical and Calorimetrymentioning
confidence: 99%
“…Metal oxide surface coatings such as Al 2 O 3 have been found to improve the stability of this interface, mitigate electrolyte oxidation, improve cycling performance and scavenge HF. [4][5][6][7][8] Selected ratios of transition metals in Li(Ni 1-x-y Mn x Co y )O 2 (NMC) positive electrodes can also lower the reactivity of the electrode surface with electrolyte at high potentials. 9,10 Isothermal microcalorimetry is a very useful tool to probe reactions in electrochemical cells in-situ in a non-destructive manner.…”
mentioning
confidence: 99%
“…[16][17][18][19] Another approach to improve cell stability is the application of an inorganic coating onto the NMC surface. [23][24][25][26][27][28][29] For example, Arumugam et al reported that a surface coating of Al 2 O 3 greatly improves NMC622/graphite cell performance. 24 Whereas both of these approaches have proven to be quite valuable, further improvements to the lifetime of NMC-containing cells at high voltages are still desired.…”
mentioning
confidence: 99%